General Concepts for the Creation of a National Automated Information System for Policlinical Services - Tutuenkov, N. G.; Kotchev, L. N.; Rashkova, K. R.; Kelbetcheva, V. P. (Methods of Information in Medicine, 1975)
The authors present a system which is designed to cover statistically the roughly 50 million policlinical services rendered annually in Bulgaria, for the purpose of planning and as proof of the activities in this field. The principle underlying the system was tested in the region of Plovdiv.
Keywords: Information System; Policlinical Services